ByzRev 06.2024.063: Fotini Kondyli, Rural Communities in Late Byzantium: Resilience and Vulnerability in the Northern Aegean.: Cambridge: Cambridge University Press 2022. 302 pp. - Murdzhev, Pavel (The Byzantine Review, 2024)
Fotini Kondyli, Rural Communities in Late Byzantium: Resilience and Vulnerability in the Northern Aegean. Cambridge: Cambridge University Press 2022. 302 pp. – ISBN 978-1-10-884549-6